A concepção de socialismo do Movimento dos Trabalhadores Rurais Sem-Terra MST. - Fernandes, Elaine Nunes Silva (2008)
The present study aimed to realize which Landless Farm Workers Movement (Movimento dosTrabalhadores Rurais Sem Terra - MST) conception about socialism. Thus, through the purpose that the dialectical method nowadays is the unique capable to unmask the social reality once these one understand this scenario as an articulated totality in a processual way. Aiming at to reach our objective we search to understand at a first moment the origin of the agrarian concentration in Brazil and the reasons that had made impracticable the accomplishment of the agrarian reform in our country. At this moment, we intent to show that as well as the peasant leagues the MST is a result of the agricultural workers fights and protests process against the Brazilian agrarian reality. In the second part of our work, we intend to perceive the theoretical reasons that had hindered the construction of the socialism. In this stage of the research, we dwelled on the Russian experience. In our understanding, this one is the main source of MST inspiration when they refer to socialist society. Objectifying to analyze if it has a real consonance between the Marx and MST thought, in this chapter we still made a brief explanation of the Marxists theoretical fundamentals about socialism. Finally, in the third and last chapter of this study, we analyze the texts of the MST, aiming at perceive the Movement concept of socialism. Among others aspects the research revealed that the Movement concept of socialism is, as most of the Left today, incurring in to error of attribute to State the conduction of the revolutionary process in detriment of work. The Movement understands that the socialism construction will be guided by the state power under command of the workers. However, the revolutionary process will be able to still happen in this social order through individuals subjective change. Our main conclusion due to the fact that in according to the Marxist theory these statement incur in a great mistake from the MST, once they attributes to State and individuals the construction of a new societal order that just can be reached by the definitive implantation of the work associated by workers.